Orally administered whey proteins have comparable effect on C-peptide secretion in healthy subjects as standard C-peptide stimulation tests - Wildová, Elena; Dlouhý, Pavel; Kraml, Pavel; Rambousková, Jolana; Šmejkalová, Vladimíra; Potočková, Jana; Anděl, Michal (Physiological research, 2013)
Our study compared total C-peptide secretion after administration of whey proteins and whey proteins in combination with glucose with results of classical tests assessing beta cell function in the pancreas of healthy individuals. Eight young, healthy (7 males, 1 female; aged 20-26 years), non-obese (BMI: 17-25.9 kg/m²) participants with normal glucose tolerance underwent six C-peptide secretion tests. Three secretion tests measured C-peptide response to orally administered substances: whey proteins only (OWT), whey proteins with glucose (OWGT) and glucose only (OGTT); while three secretion tests measured C-peptide response to intravenously administered substances: arginine (AST), glucagon (GST) and glucose (IVGTT). OWT stimulated a greater (93 %, p<0.05) C-peptide response than AST and a 64 % smaller response (p<0.05) than OGTT. OWT also showed lower variability (p<0.05) in C-peptide responses compared to OWGT and OGTT. The greatest total C-peptide response was induced by OWGT (36 % higher than glucose). OWT consistently increased C-peptide concentrations with lower individual variability, while insignificantly increasing glucose levels. Results of this study suggest that both dietology and beta-cells capacity testing could take advantage of the unique property of whey proteins to induce C-peptide secretion.
Keywords: glukózový toleranční test; Stimulation, Chemical; krevní glukóza; Milk Proteins; inzulin; plocha pod křivkou; lidé; ženské pohlaví; C-peptid; Glucose Tolerance Test; Blood Glucose; Area Under Curve; Female; mužské pohlaví; Young Adult; Insulin; arginin; Adult; Glucagon; mléčné bílkoviny; C-Peptide; chemická stimulace; Arginine; klinické křížové studie; Cross-Over Studies; glukagon; Humans; dospělí; Male; mladý dospělý